2022
DOI: 10.3389/fcimb.2022.907239
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gut Microbiota Compositions Related With the Severity of Major Depressive Disorder

Abstract: ObjectiveIncreasing evidence shows a close relationship between gut microbiota and major depressive disorder (MDD), but the specific mechanisms remain unknown. This study was conducted to explore differential gut microbiota compositions related to the severity of MDD.MethodsHealthy controls (HC) (n = 131) and MDD patients (n = 130) were included. MDD patients with Hamilton Depression Rating Scale (HDRS) score <25 and ≥25 were assigned into moderate (n = 72) and severe (n = 58) MDD groups, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
(96 reference statements)
1
8
0
Order By: Relevance
“…If microbiota factors contribute to depression in people, then the microbiome (a genetic census of the microbiota) of depressed patients may display distinct signatures from that of healthy controls. Indeed, by comparing the microbiome of depressed patients versus healthy controls, changes in the abundance of certain bacteria taxa have been reported in many studies (Jiang et al, 2015;McGuinness et al, 2022;Radjabzadeh et al, 2022;Zhong et al, 2022). In agreement with the discovery of metagenomic signatures of depression, metaproteomics and metabolomics studies in mice and men also reveal significant depression-associated differences at the level of microbial-associated peptides and metabolites, the classes of compounds that interface microbe-host interactions (Yu et al, 2017;Chen et al, 2018;Valles-Colomer et al, 2019;Wu et al, 2020).…”
Section: Microbial Factors In Depressionmentioning
confidence: 72%
“…If microbiota factors contribute to depression in people, then the microbiome (a genetic census of the microbiota) of depressed patients may display distinct signatures from that of healthy controls. Indeed, by comparing the microbiome of depressed patients versus healthy controls, changes in the abundance of certain bacteria taxa have been reported in many studies (Jiang et al, 2015;McGuinness et al, 2022;Radjabzadeh et al, 2022;Zhong et al, 2022). In agreement with the discovery of metagenomic signatures of depression, metaproteomics and metabolomics studies in mice and men also reveal significant depression-associated differences at the level of microbial-associated peptides and metabolites, the classes of compounds that interface microbe-host interactions (Yu et al, 2017;Chen et al, 2018;Valles-Colomer et al, 2019;Wu et al, 2020).…”
Section: Microbial Factors In Depressionmentioning
confidence: 72%
“…At the genus level, the abundance of Alistipes , Alloprevotella , and Lleibacterium decreased significantly, and these changes were also observed in mice receiving FMT treatment. Alistipes , belonging to the family Rikenellaceae , has been shown to be significantly associated with depression ( Jiang et al, 2015 ; Zhong et al, 2022 ). Alistipes has also been linked to depression-like phenotypes in other mood disorders ( Domènech et al, 2022 ; Zhang et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that this bacterium is involved in the production of butyric acid, the main SCFA produced by the intestinal flora [ 80 ]. Moreover, in the studies involving patients with major depressive disorder (MDD), this bacterium was identified as a potential MDD biomarker [ 81 ]. Similarly, Zhou et al [ 82 ] showed that both Faecalibacterium and Butyricicoccus may be important in diagnosing and treating patients suffering from postpartum depression.…”
Section: Discussionmentioning
confidence: 99%